Preparation method of Sb2S3 / MoS2 composite wave-absorbing material

Through the preparation of Sb2S3/MoS2 composite materials, the core-shell structure is generated by hydrothermal method, which solves the problems of insufficient electromagnetic response capability and narrow absorption bandwidth of antimony sulfide-based materials, and achieves a wide-band absorption effect with simple process and low cost. It is suitable for Resolution of electromagnetic interference and radiation.

CN119193107APending Publication Date: 2024-12-27YANCHENG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410885385.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-03
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing antimony sulfide-based materials have problems such as insufficient electromagnetic response capability and narrow absorption bandwidth in the field of electromagnetic wave absorption, and the preparation method is complex and costly.

Method used

Using the preparation method of Sb2S3/MoS2 composite absorbing material, antimony chloride is reacted with L-cysteine ​​and sodium sulfide nohydrate to form rod-shaped antimony sulfide nanomaterial through hydrothermal method, and is then used to reheat molybdenum dihydrate. Sodium acid and thiourea were treated to form a rod-shaped Sb2S3/MoS2 composite material with a core-shell structure.

Benefits of technology

It realizes a simple process and low cost preparation process. The material has a wide band absorption capacity, reduces the matching thickness and filling ratio, and improves the electromagnetic wave absorption performance. It is suitable for solving electromagnetic interference and radiation problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193107A_ABST
    Figure CN119193107A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a Sb2S3 / MoS2 composite wave-absorbing material, which comprises the following steps: dissolving antimony chloride, L-cysteine and sodium sulfide nonahydrate in deionized water, uniformly stirring to obtain an orange mixed solution, transferring the orange mixed solution into a reaction kettle, carrying out hydrothermal reaction to obtain an antimony sulfide nano-material, dissolving the antimony sulfide nano-material and sodium molybdate dihydrate in deionized water, and carrying out hydrothermal reaction to obtain the Sb2S3 / MoS2 composite wave-absorbing material. And adding thiourea under rapid stirring to obtain a mixed solution, transferring the mixed solution into a reaction kettle, heating to carry out hydrothermal reaction, cooling, washing, filtering and drying to obtain the product. The method is simple in process and low in raw material cost, the prepared wave-absorbing material is of a rod-shaped structure, the transmission path of electromagnetic waves is prolonged, dissipation of electromagnetic wave energy is increased, and meanwhile the defects that a traditional antimony sulfide material is high in filling rate and low in conductivity are overcome. The wave-absorbing material prepared by the method has the characteristics of wide absorption frequency band and small matching thickness, and has a better application prospect in the field of electromagnetic wave absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave absorbing materials, and in particular relates to a method for preparing a Sb2S3 / MoS2 composite wave absorbing material. Background Art

[0002] In the middle of the 19th century, some phenomena and behaviors of electromagnetic waves attracted people's attention. Scientists found that the control and management of electromagnetic waves could better realize the transmission of signals, and began to study absorbing materials. In the middle of the 20th century, absorbing materials began to be gradually used in military fields such as stealth aircraft and stealth missiles. Nowadays, with the development of radar technology and communication technology, the popularization of 5g signals, life is also full of electromagnetic signals. Some smart wearable devices such as mobile phones and watches are inseparable from the influence of electromagnetic waves. If people are in this strong electromagnetic wave environment for a long time, they will have symptoms such as headaches, inattention, and drowsiness. Strong electromagnetic radiation will also aggravate cardiovascular diseases and cause problems such as dysfunction of the nervous system. Therefore, in recent years, domestic and foreign countries have been highly committed to developing thinner, lighter, wider, and stronger electromagnetic wave absorbing materials to meet the needs of the military field and daily production and life.

[0003] Transition metal sulfides have excellent electrochemical, mechanical and optical properties due to their special structure, and are widely used in nanoelectronic devices, electrochemical energy storage and other fields. Antimony sulfide, as a transition metal sulfide, has been favored by researchers due to its high theoretical specific capacity, single stable phase, narrow band gap (1.5-2.2eV) and abundant raw materials. However, antimony sulfide itself is non-magnetic and has low conductivity, resulting in insufficient electromagnetic response ability, which limits its application in the field of electromagnetic wave absorption.

[0004] Researchers have provided some modification strategies for these inherent defects of antimony sulfide. For example, antimony sulfide can be compounded with dielectric materials or magnetic materials to regulate the electromagnetic parameters of the material, thereby achieving the purpose of optimizing the absorbing performance and diversifying the absorbing mechanism. However, the existing preparation methods of antimony sulfide-based materials are generally complicated to operate, the morphology of the synthesized antimony sulfide is unstable, and when used as an absorbing material, there are problems such as insufficient electromagnetic response and narrow absorption bandwidth. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a Sb2S3 / MoS2 composite absorbing material in order to address the problems of insufficient electromagnetic response capability and narrow absorption bandwidth of antimony sulfide-based materials prepared by prior art. The method has a simple preparation process, is easy to control and has low production cost. The prepared Sb2S3 / MoS2 absorbing material has the characteristics of thin matching thickness and wide effective absorption bandwidth.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing a Sb2S3 / MoS2 composite absorbing material comprises the following steps:

[0008] S1. Dissolve antimony chloride, L-cysteine ​​and sodium sulfide nonahydrate in deionized water and stir evenly to obtain an orange mixed solution;

[0009] S2, transferring the mixed solution to a reactor, heating it for hydrothermal reaction, cooling it after completion, and then washing, filtering and drying it to obtain antimony sulfide nanomaterials;

[0010] S3, adding antimony sulfide nanomaterial and sodium molybdate dihydrate into deionized water, stirring until completely dissolved, and then adding thiourea under rapid stirring to obtain a mixed solution;

[0011] S4. Transfer the mixed solution to a reactor, heat it up for hydrothermal reaction, cool it after completion, and then wash, filter and dry it to obtain a Sb2S3 / MoS2 composite absorbing material.

[0012] Preferably, in step S1, the molar ratio of antimony chloride to L-cysteine ​​is 3:(7-9).

[0013] Preferably, in step S1, the molar ratio of antimony chloride to sodium sulfide nonahydrate is 3:(7-9).

[0014] Preferably, in step S2, the heating rate is 5 to 8°C / min, the temperature of the hydrothermal reaction is 170 to 190°C, and the reaction time is 10 to 14 hours.

[0015] Preferably, in step S2, the drying temperature is 50-70° C. and the drying time is 12-14 hours.

[0016] Preferably, in step S3, the molar ratio of the antimony sulfide nanomaterial to sodium molybdate dihydrate is 1:(1-4).

[0017] Preferably, in step S3, the molar ratio of the antimony sulfide nanomaterial to thiourea is 1:(5-12).

[0018] Preferably, in step S3, the rotation speed of the rapid stirring is 600-800 rpm.

[0019] Preferably, in step S4, the heating rate is 5 to 8°C / min, the temperature of the hydrothermal reaction is 190 to 210°C, and the reaction time is 22 to 26 hours.

[0020] A Sb2S3 / MoS2 composite material prepared by the method.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention provides a method for preparing a Sb2S3 / MoS2 composite absorbing material. First, antimony chloride is used as a raw material, L-cysteine ​​and sodium sulfide nonahydrate are used as an organic sulfur source and an inorganic sulfur source, respectively, and a rod-shaped antimony sulfide material is prepared by a hydrothermal method. Subsequently, sodium molybdate dihydrate and thiourea are introduced for secondary hydrothermal treatment to prepare a rod-shaped Sb2S3 / MoS2 composite material with a core-shell structure. The method has the advantages of simple process and low cost, and the rod-shaped structure of the material is also conducive to extending the transmission path of electromagnetic waves, increasing the dissipation of electromagnetic wave energy, and avoiding the disadvantages of high filling rate and low conductivity of traditional antimony sulfide materials.

[0023] 2. The present invention prepares a rod-shaped Sb2S3 / MoS2 composite material with a core-shell structure through two hydrothermal processes. The material can effectively improve the absorption bandwidth, reduce the matching thickness, and the filling ratio, and has good development prospects.

[0024] 3. The Sb2S3 / MoS2 composite material prepared by the present invention has a 1D / 2D composite structure, which can produce abundant heterogeneous interfaces and bring better performance. When the matching thickness is 2.00 mm, the filling amount is 60%, and the frequency is 14.80 GHz, the minimum reflection loss (RL min ) is -21.90dB, and the effective absorption bandwidth (EAB) is 6.40GHz (10.96-17.36GHz). Therefore, the Sb2S3 / MoS2 composite material prepared by the present invention is a wide-band absorbing material, which is beneficial to solving the problems of electromagnetic interference and electromagnetic radiation and improving the performance and reliability of electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 XRD patterns of the Sb2S3 / MoS2 composite absorbing materials prepared in Examples 1-3 and the Sb2S3 absorbing material prepared in Comparative Example 1;

[0026] Figure 2 SEM images of the Sb2S3 / MoS2 composite absorbing material prepared in Example 2 and the Sb2S3 absorbing material prepared in Comparative Example 1;

[0027] Figure 3 The reflection loss curve of the Sb2S3 / MoS2 composite absorbing material prepared in Example 1 at a thickness of 1.0 to 5.5 mm;

[0028] Figure 4 The reflection loss curve of the Sb2S3 / MoS2 composite absorbing material prepared in Example 2 at a thickness of 1.0 to 5.5 mm;

[0029] Figure 5This is the reflection loss curve of the Sb2S3 / MoS2 composite absorbing material prepared in Example 3 at a thickness of 1.0 to 5.5 mm. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0031] Example 1

[0032] A method for preparing a Sb2S3 / MoS2 composite absorbing material comprises the following steps:

[0033] S1. Dissolve 0.684 g of antimony chloride, 0.969 g of L-cysteine ​​(C3H7NO2S) and 1.921 g of sodium sulfide nonahydrate in 80 mL of deionized water, and stir for 3 h to obtain an orange-yellow mixed solution.

[0034] S2, transferring the mixed solution to a reactor, placing the reactor in an electric blast drying oven, heating the temperature to 180°C at a heating rate of 6°C / min, keeping the temperature for reaction for 12 hours, cooling to room temperature after the reaction, washing the reaction product with anhydrous ethanol and distilled water alternately three times, filtering to obtain a black solid product, and drying at 60°C for 12 hours to obtain antimony sulfide nanomaterials;

[0035] S3, adding 0.100 g of antimony sulfide nanomaterial and 0.101 g of sodium molybdate dihydrate to 30 mL of deionized water, stirring until completely dissolved, then adding 0.119 g of thiourea (CH4N2S) under rapid stirring, and continuing to stir for 30 min to obtain a mixed solution;

[0036] S4. Transfer the mixed solution to a polytetrafluoroethylene reactor, and then place the reactor in an electric heated air drying oven, heat it to 200°C at a heating rate of 6°C / min, and keep it warm for 24 hours. After the reaction is completed, cool it to room temperature, wash the reaction product with anhydrous ethanol and distilled water alternately for three times, filter it to obtain a black solid product, and dry it at 80°C for 12 hours to obtain the Sb2S3 / MoS2 absorbing material, recorded as Sb2S3 / MoS2-1.

[0037] Example 2

[0038] A method for preparing a Sb2S3 / MoS2 composite absorbing material comprises the following steps:

[0039] S1. Dissolve 0.684 g of antimony chloride, 0.969 g of L-cysteine ​​(C3H7NO2S) and 1.921 g of sodium sulfide nonahydrate in 80 mL of deionized water, and stir for 3 h to obtain an orange-yellow mixed solution.

[0040] S2, transferring the mixed solution to a reactor, placing the reactor in an electric blast drying oven, heating the temperature to 180°C at a heating rate of 6°C / min, keeping the temperature for reaction for 12 hours, cooling to room temperature after the reaction, washing the reaction product with anhydrous ethanol and distilled water alternately three times, filtering to obtain a black solid product, and drying at 60°C for 12 hours to obtain antimony sulfide nanomaterials;

[0041] S3, adding 0.100 g of antimony sulfide nanomaterial and 0.151 g of sodium molybdate dihydrate to 30 mL of deionized water, stirring until completely dissolved, then adding 0.178 g of thiourea (CH4N2S) under rapid stirring, and continuing to stir for 30 min to obtain a mixed solution;

[0042] S4. Transfer the mixed solution to a polytetrafluoroethylene reactor, and then place the reactor in an electric heated blast drying oven, heat it to 200°C at a heating rate of 6°C / min, and keep it warm for 24 hours. After the reaction is completed, cool it to room temperature, wash the reaction product with anhydrous ethanol and distilled water alternately for three times, filter it to obtain a black solid product, and dry it at 80°C for 12 hours to obtain the Sb2S3 / MoS2 absorbing material, recorded as Sb2S3 / MoS2-2.

[0043] Example 3

[0044] A method for preparing a Sb2S3 / MoS2 composite absorbing material comprises the following steps:

[0045] S1. Dissolve 0.684 g of antimony chloride, 0.969 g of L-cysteine ​​(C3H7NO2S) and 1.921 g of sodium sulfide nonahydrate in 80 mL of deionized water, and stir for 3 h to obtain an orange-yellow mixed solution.

[0046] S2, transferring the mixed solution to a reactor, placing the reactor in an electric blast drying oven, heating the temperature to 180°C at a heating rate of 6°C / min, keeping the temperature for reaction for 12 hours, cooling to room temperature after the reaction, washing the reaction product with anhydrous ethanol and distilled water alternately three times, filtering to obtain a black solid product, and drying at 60°C for 12 hours to obtain antimony sulfide nanomaterials;

[0047] S3, adding 0.100 g of antimony sulfide nanomaterial and 0.227 g of sodium molybdate dihydrate to 30 mL of deionized water, stirring until completely dissolved, then adding 0.268 g of thiourea (CH4N2S) under rapid stirring, and continuing to stir for 30 min to obtain a mixed solution;

[0048] S4. Transfer the mixed solution to a polytetrafluoroethylene reactor, and then place the reactor in an electric heated air drying oven, heat it to 200°C at a heating rate of 6°C / min, and keep it warm for 24 hours. After the reaction is completed, cool it to room temperature, wash the reaction product with anhydrous ethanol and distilled water alternately for three times, filter it to obtain a black solid product, and dry it at 80°C for 12 hours to obtain the Sb2S3 / MoS2 absorbing material, recorded as Sb2S3 / MoS2-3.

[0049] Comparative Example 1

[0050] A method for preparing a Sb2S3 absorbing material comprises the following steps:

[0051] S1. Dissolve 0.684 g of antimony chloride, 0.969 g of L-cysteine ​​(C3H7NO2S) and 1.921 g of sodium sulfide nonahydrate in 80 mL of deionized water, and stir for 3 h to obtain an orange-yellow mixed solution.

[0052] S2. Transfer the mixed solution to a reactor, and then place the reactor in an electric heated blast drying oven, heat it to 180°C at a heating rate of 6°C / min, and keep it warm for 12 hours. After the reaction is completed, cool it to room temperature, wash the reaction product with anhydrous ethanol and distilled water alternately for three times, and obtain a black solid product after filtration. After drying at 60°C for 12 hours, the Sb2S3 absorbing material is obtained.

[0053] Performance Test:

[0054] 1. The phase structure of the Sb2S3 / MoS2 composite absorbing materials prepared in Examples 1-3 and the Sb2S3 absorbing material prepared in Comparative Example 1 was analyzed using XRD.

[0055] Figure 1 The XRD diagrams of the Sb2S3 / MoS2 composite absorbing materials prepared in Examples 1-3 and the Sb2S3 absorbing material prepared in Comparative Example 1 are shown in FIG. Figure 1 (a) is the XRD pattern of the Sb2S3 absorbing material prepared in Comparative Example 1, Figure 1 (b) is the XRD pattern of the Sb2S3 / MoS2 composite absorbing material prepared in Example 1-3. Figure 1 (a) It can be seen that Sb2S3 was successfully prepared. Figure 1(b) It can be seen that the diffraction peaks of Sb2S3 at 2θ=15.6, 17.5, 22.2, 24.8, 29.2, 32.3, 33.3, 39.5, 42.9, 46.7 and 54.1° belong to the (020), (120), (220), (130), (211), (301), (041), (421), (501) and (123) crystal planes of Sb2S3 (JCPDS No.42-1393). At the same time, with the increase of molybdenum disulfide content, there are more obvious characteristic peaks of molybdenum disulfide (JCPDS No.37-1492) at 14.4 and 39.5°, and the corresponding crystal planes are (002) and (103). The above analysis shows the successful preparation of Sb2S3 / MoS2 composite materials.

[0056] 2. The microstructure of the Sb2S3 / MoS2 composite absorbing material prepared in Example 2 and the Sb2S3 absorbing material prepared in Comparative Example 1 were analyzed by SEM.

[0057] Figure 2 The SEM images of the Sb2S3 / MoS2 composite absorbing material prepared in Example 2 and the Sb2S3 absorbing material prepared in Comparative Example 1 are shown in FIG. Figure 2 (a) is the SEM image of the Sb2S3 absorbing material prepared in Comparative Example 1, Figure 2 (b) Figure 2 (c) and Figure 2 (d) is the SEM image of the Sb2S3 / MoS2 composite absorbing material prepared in Example 2 at different magnifications. Figure 2 As shown in (a), antimony sulfide has a rod-like structure with an average length of about 3 μm and a diameter between 100-200 nm. The nanorods are stacked in an interlaced manner. Figure 2 (b) Figure 2 (c) and Figure 2 (d) It can be seen that after the second hydrothermal treatment, antimony sulfide maintains its original rod-like structure, while molybdenum disulfide grows evenly on the surface of antimony sulfide in the form of nanosheets, and the diameter of the composite material reaches 400nm. The unique sheet structure forms more heterogeneous interfaces, which is conducive to multiple reflections and scattering of electromagnetic waves inside the material, extending the dissipation path of electromagnetic waves and enhancing the electromagnetic wave absorption capacity.

[0058] 3. Use a vector network analyzer to analyze the electromagnetic parameters of the sample and then calculate its absorption performance.

[0059] Figure 3 The reflection loss curve of the Sb2S3 / MoS2 composite absorbing material prepared in Example 1 at a thickness of 1.0 to 5.5 mm; Figure 4The reflection loss curve of the Sb2S3 / MoS2 composite absorbing material prepared in Example 2 at a thickness of 1.0 to 5.5 mm; Figure 5 This is the reflection loss curve of the Sb2S3 / MoS2 composite absorbing material prepared in Example 3 with a thickness of 1.0 to 5.5 mm. Figure 3 It can be seen that when the thickness of Sb2S3 / MoS2-1 (Sb2S3 / MoS2 composite absorbing material prepared in Example 1) is 2.00 mm, RL min The value is -22.16dB; when the thickness is 1.50mm, the EAB value is 4.72GHz (11.20-15.92GHz). Figure 4 It can be seen that the EAB value of Sb2S3 / MoS2-2 (Sb2S3 / MoS2 composite absorbing material prepared in Example 2) is significantly improved to 6.40 GHz, and the RL min The value is not greatly affected, reaching -21.91dB at -14.80GHz. The improvement in wave absorption performance is attributed to strong electromagnetic attenuation and good impedance matching characteristics. The introduction of molybdenum disulfide improves the dielectric properties of antimony sulfide and increases the electromagnetic response ability of antimony sulfide. In addition, the flaky molybdenum disulfide and the rod-shaped antimony sulfide form a heterogeneous interface, which promotes interface polarization, and the unique flaky structure prolongs the transmission path of electromagnetic waves, and also achieves the purpose of electromagnetic wave dissipation. Figure 5 It can be seen that as the content of molybdenum disulfide in Sb2S3 / MoS2-3 (Sb2S3 / MoS2 composite absorbing material prepared in Example 3) continues to increase and gradually exceeds the content of antimony sulfide, the RL of the composite material min and EAB values ​​are seriously reduced. At 1.50 mm, RL min The value is only -11.63dB at 13.28GHz, and the EAB value is 2.40GHz (12.24-14.64GHz). This is because molybdenum disulfide increases the conductivity of antimony sulfide, but excessive molybdenum disulfide makes the conductivity of the composite material too high, resulting in impedance mismatch, and electromagnetic waves cannot enter the interior of the material, so the absorption performance of Sb2S3 / MoS2-3 is not satisfactory. Therefore, the absorption performance of electromagnetic waves does not increase linearly with the increase of materials, but is the result of the combined effect of multiple factors. Therefore, Sb2S3 / MoS2-2 has good electromagnetic wave absorption performance, meeting the requirements of "thin, light, wide and strong" for electromagnetic wave absorption materials.

[0060] Finally, it should be noted that the above description is only a preferred example of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a Sb2S3 / MoS2 composite absorbing material, characterized in that: The steps include: S1. Dissolve antimony chloride, L-cysteine ​​and sodium sulfide nonahydrate in deionized water and stir evenly to obtain an orange mixed solution; S2, transferring the mixed solution to a reactor, heating it for hydrothermal reaction, cooling it after completion, and then washing, filtering and drying it to obtain antimony sulfide nanomaterials; S3, adding antimony sulfide nanomaterial and sodium molybdate dihydrate into deionized water, stirring until completely dissolved, and then adding thiourea under rapid stirring to obtain a mixed solution; S4, transferring the mixed solution to a reactor, heating it for hydrothermal reaction, cooling it after completion, and then washing, filtering and drying it to obtain a Sb2S3 / MoS2 composite absorbing material; In step S3, the molar ratio of the antimony sulfide nanomaterial to sodium molybdate dihydrate is 1:(1-4).

2. The method for preparing the Sb2S3 / MoS2 composite absorbing material according to claim 1, characterized in that: In step S1, the molar ratio of antimony chloride to L-cysteine ​​is 3:(7-9).

3. The method for preparing the Sb2S3 / MoS2 composite absorbing material according to claim 1, characterized in that: In step S1, the molar ratio of antimony chloride to sodium sulfide nonahydrate is 3:(7-9).

4. The method for preparing the Sb2S3 / MoS2 composite absorbing material according to claim 1, characterized in that: In step S2, the heating rate is 5-8°C / min, the temperature of the hydrothermal reaction is 170-190°C, and the reaction time is 10-14h.

5. The method for preparing the Sb2S3 / MoS2 composite absorbing material according to claim 1, characterized in that: In step S2, the drying temperature is 50-70°C and the drying time is 12-14 hours.

6. The method for preparing the Sb2S3 / MoS2 composite absorbing material according to claim 1, characterized in that: In step S3, the molar ratio of the antimony sulfide nanomaterial to thiourea is 1:(5-12).

7. The method for preparing the Sb2S3 / MoS2 composite absorbing material according to claim 1, characterized in that: In step S3, the rotation speed of the rapid stirring is 600-800 rpm.

8. The method for preparing the Sb2S3 / MoS2 composite absorbing material according to any one of claims 1 to 7, characterized in that: In step S4, the heating rate is 5-8°C / min, the temperature of the hydrothermal reaction is 190-210°C, and the reaction time is 22-26h.

9. A Sb2S3 / MoS2 composite absorbing material prepared by the method according to any one of claims 1 to 8.